Analisis Bibliometrik dari Corporate Social Responsibility sebagai Variabel Strategi Praktik Penghapusan Pajak - Febria Epti Anjani Ariputri; Sri Andriani (AKUNTANSI 45, 2025)
Using bibliometric techniques, this study attempts to examine the evolution and relationship between tax avoidance and Corporate Social Responsibility (CSR). Using Publish of Perish software, secondary data were collected from indexed scientific publications between 2020 and 2024. VOSviewer software was used to track the relationship between research topics and trends as part of a quantitative descriptive study. The analysis findings show that more than 1,000 publications categorized into several main groups discuss CSR and tax avoidance. The visualization shows that CSR is often used by businesses to address social issues, increase credibility, and, in some cases, serve as a strategy to implement tax practices. This study makes a significant contribution to the accounting and tax literature by highlighting the direction, focus, and gaps in research that are still incomplete. All of these can be used by academics, practitioners, and others to better understand CSR and tax strategies in the business world.